ANALYSIS OF THE TECHNOLOGY ACCEPTANCE LEVEL OF VIRTUAL REALITY TECHNOLOGY IN THE LEARNING PROCESS OF THE FACULTY OF PSYCHOLOGY CIPUTRA UNIVERSITY - Gunadisastra, Stefanus; Choiruddin, Achmad (International Business Management - Universitas Ciputra, 2025)
This study explores the acceptance of Virtual Reality (VR) technology in psychology education at Ciputra University. In the 2023/2024 academic year, VR was introduced for phobia therapy learning, prompting the need to measure its acceptance among students who were the first to receive instruction with VR technology. Understanding the acceptance of VR technology is crucial for informing academic and operational strategies. Using the Technology Acceptance Model 3 (TAM3), this study investigates factors such as perceived usefulness, ease of use, subjective norm, enjoyment, attitude, and behavioral intention, which have been used in previous research. A survey method involving 60 Bachelor students in Psychology in the Ciputra University will gather data, analyzed through Structural Equation Model Partial Least Square (SEM-PLS) via Smart PLS to identify significant factors affecting VR acceptance. The research aims to provide insights into barriers and motivators for VR adoption in academia, facilitating the development of effective strategies for integrating VR into psychology education. Ultimately, this study aims to enhance learning experiences and promote innovative teaching methods using VR technology. This study examines the relationships between various factors in the context of Virtual Reality (VR) technology adoption for learning. It reveals that subjective norms influence perceived usefulness, indicating that others' opinions can enhance students' perception of the benefits of VR technology. Moreover, perceived enjoyment affects perceived ease of use, indicating that students' comfort and enjoyment with the technology impact their perception of its ease of use. Ease of use, in turn, influences perceived usefulness and learning effectiveness, highlighting the importance of user-friendly VR devices for effective learning. Interestingly, ease of use does not directly affect attitude toward use, suggesting that the ease of using VR technology may not significantly impact individuals' motivation to explore its features. However, attitude toward use positively influences behavioral intention, indicating that individuals' interest in VR technology features influences their intention to use it for learning and recommend it to others. Overall, the study emphasizes the importance of social influence, user experience, and attitude in shaping individuals' intention to use VR technology for learning. It suggests expanding the research scope to include a broader range of respondents and additional supporting variables to further understand the factors affecting successful learning with VR technology across various disciplines.